Analysis of Work Ethic, Integrity, Supervision, and Communication on the Performance of Employees at the Dinas Perhubungan Province Jawa Timur - Wulandari, Anita; Sukarno, Gendut (PT FORMOSA CENDEKIA GLOBAL, 2024)
In the era of globalization with the integration of economies, politics, and cultures between countries, Civil Servants (PNS) must adapt to an increasingly complex and dynamic work environment. One of the most noticeable impacts of globalization is the increasing demand for more efficient, responsive, and transparent public services. This study aims to determine the influence of Work Ethic, Integrity, Supervision, and Communication on the performance of employees at the Department of Transportation in East Java Province. This research employs a quantitative research type, with variable measurement using a Likert scale. The sample resulting in a sample of 83 employees. The data analysis technique used is the Partial Least Square (PLS) method. The results show that Work Ethic has a positive and significant effect on employee performance, Integrity has a positive and significant effect on performance, Supervision has a positive but not significant effect on performance, and Communication has a positive and significant effect on performance.